First report of epimeletic behaviour in a Black Sea harbour porpoise (Phocoena phocoena relicta Abel, 1905) towards a dead calf - Korosteleva, A.V.; Postnikova, A.N.; Suvorova, I.V.; Kuklin, K.G. (Водные биоресурсы и среда обитания, 2022)
The term “epimeletic” (“caregiving”) is used to represent a range of cetacean behavioural patterns directed at dead or distressed conspecifics, including accompanying, lifting to the surface, and protecting from apparent threats. This behaviour has been described in the literature for various cetacean species; however, such reports have not yet involved members of the Phocoenidae family. The Black Sea harbour porpoise (Phocoena phocoena relicta Abel, 1905) is an endangered subspecies that is endemic to the Black Sea. Despite the proximity of its habitats to the coast, many aspects of its biology, including behaviour, remain poorly studied. In this paper, we present the first report of epimeletic behaviour in a wild Black Sea harbour porpoise towards a dead calf. The observation took place during the marine mammal stranding network operation off the Crimean coast in July 2018. A recently deceased harbour porpoise calf was found floating on the water surface close to the shore, where it was escorted by a live adult porpoise. We performed a physical examination and an autopsy of the calf, which revealed pulmonary edema, esophagitis, and enteritis. Milk was present in the stomach, indicating recent feeding. We assume that the adult individual could be a lactating female. This observation is probably the only indication to date of the possibility of wild harbour porpoises showing epimeletic behaviour towards dead calves, which emphasizes the importance of conducting wider in-depth studies on their behavioural characteristics and social interaction. Термин «эпимелетический» («поддерживающий») используется для обозначения ряда поведенческих паттернов китообразных по отношению к мертвым или умирающим сородичам, включая их сопровождение, поддержку на поверхности воды и попытки защиты от очевидной угрозы. В литературе данный тип поведения был описан для различных видов китообразных, однако подобные сообщения еще не затрагивали представителей семейства Phocoenidae. Черноморская морская свинья (Phocoena phocoena relicta ...